kondisi MEKANISME ANGIN TOPAN DAN DAMPAKNYA PADA LINGKUNGAN: mekanisme angin topan dan dampaknya pada lingkungan serta upaya pencegahannya - prasetyo, Agung adi prasetyo; Sudarti, Sudarti (Fakultas Teknik Universitas Hamzanwadi, 2024)
Natural disasters are natural phenomena that can occur anytime and anywhere. Natural disasters have a negative impact on society, both in the form of property damage and loss of life, environmental damage, and also impact on various aspects of human life such as the economy, socio-culture, security, etc. A hurricane is a rotating weather system with very strong wind speeds, usually above 119 km/h (74 mi/h). Hurricanes form in tropical or subtropical oceans and move towards land. Hurricanes have a spiral-shaped structure with an eye in the center. The eye of a typhoon is the area with the lowest air pressure and relatively calm winds. The closer to the eye, the stronger the wind. Storms are formed due to the large temperature difference between the ocean and land, as well as high air humidity. Heat from the ocean causes air to rise, creating an area of ​​low pressure that draws wind from the surrounding area. Hurricanes can cause severe damage, including building damage, fallen trees, flooding, and tidal waves. Hurricanes can also cause death and severe infrastructure damage. Typhoons have various names in various parts of the world, such as cyclones in the Indian Ocean, typhoons in the West Pacific Ocean, and typhoons in the Atlantic Ocean. The aim of this research is to determine the mechanisms and impacts caused by typhoons on the environment. The research method used in this research is a literature study using data from various journal and book sources. To reduce the impact of natural disasters, especially typhoons, requires various efforts and cooperation from all parties to jointly find solutions to solve problems that arise as a result of these disasters. These solutions can take the form of prevention before a disaster occurs, preparedness and post-disaster recovery efforts. With real efforts and actions before, during and after a disaster, it is hoped that we will be able to prevent hurricanes from occurring in the future.